Vehicle sharing systems: A review and a holistic management framework - Selin Ataç; Nikola Obrenović; Michel Bierlaire (EURO Journal on Transportation and Logistics (EJTL), 2021)
Although different vehicle sharing systems (VSSs) use different vehicle types, the management challenges and optimization problems to be solved are similar or even the same. This observation led us to create a generalized and holistic VSS management framework, which aims to be applicable to the system using any vehicle type. The framework components, their mutual relationships, and framework tasks have been identified through a thorough and systematic literature review. Furthermore, the literature is positioned in the line with the framework. Finally, the framework and systematic literature review allowed us to identify gaps in the literature, and interesting research avenues.
Keywords: 330; Holistic management framework; Literature review; Vehicle sharing system